(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of this work was to evaluate the use of biofloc technology to reared Amazon River prawn (Macrobrachium amazonicum). One hundred Amazon River prawn juveniles were divided into two experimental units (250 L), 50 animals per each. Prawns were fed two times per day, with 3% of the prawn biomass. Dissolved oxygen and temperature were performed twice a day. Total suspended solids, pH, alkalinity, ammonia nitrogen, nitrite and nitrate were monitored twice a week. Prawns showed 77.67%, survival, 2.98 feed conversion, weekly weight gain of 0.29 g day-1, and yield of 822.0 g m-3 after six weeks of rearing. Dissolved oxygen, temperature and pH were suitable for the species, however, for some weeks, ammonia nitrogen and nitrite were higher than the limits recommended for prawn. In conclusion it is possible to use BFT to maintain and rearing Amazon River Prawn (M. amazonicum), however to improve the performance it is necessary to define nutritional requirements, as well improve the management techniques for this species in BFT.